Entre a queima e o que consome: a chama-da publicidade às mulheres - Nascimento, Christiane Moura (2011)
The woman becomes the subject through the culture. During postmodernity the rules of consumption lead the human relations, the insatiability of the whishes and the instant continuous happiness are social orders. The media transmit broadcast, especially through television, the most popular mass-media in Brazil. Through advertising everyone whatches itself on the opportunity of becoming the subject through the pictures associated to the advertised products. Our aim is to investigate the subjective formations directed woman through Brazilian advertising. This analysis has been realized using the psychoanalytic method, which on interface between psyche and culture, investigates the field of subconscious human senses. The analysis, for each advertising has been carried on through the following steps: selection of four TV advertisings, referred to women‟s cosmetics and personal hygiene products, detailed description of the pictures through a chart analysis, analysis of the arisen senses and comparison with the theoretical reference, andsynthesis of conclusion. The process of the above mentioned analysis was inspired by Herrmann, who proposes that we should let the inquired problem reveals itself in itshuman significancy,,then to lean over other, and thus to create an interpretive matrix through emerged senses on the two firsts statements; and, in this manner, part fromit (the matrix), to investigate a third problem, that reveal itself on other sense or on field‟s rupture. The first advertising reveals the fallus power circulation; in the second one, the completion‟s notion; in the third, the human distortion‟s process; and in the fourth one, the lingering of a feminine condition. To conclude we debated, through the emerged senses by the four advertisings, the postmodernity woman‟ subjective condition, passed over the absence.